THE PROBLEM OF DEFINITION OF NORMS AND RULES OF PROFESSIONAL AND PEDAGOGICAL ACTIVITY - M.P. Vasylyeva (Academy of Cognitive and Natural Sciences, 2010)
In the article realization of principle of normativity of professional con duct of teacher is analysed through description of the standards and rules of his professionally - pedagogical activity. The specific of deontological approach and feature of deontological standards is exposed in activity of representative of pe dagogical profession.